Determinants of Successful Implementation of Early Breastfeeding Initiation in RSU PKU Muhammadiyah Gamping, Yogyakarta - Nidatul Khofiyah; Fitnaningsih Endang C (Sean Institute, 2023)
Breastfeeding can accelerate the decline in IMR and at the same time improve the nutritional status of children which will ultimately improve the nutritional status of society towards achieving adequate quality of human resources. WHO and UNICEF recommend early initiation of breastfeeding (early lact on) as a life saving measure, because Early Initiation of Breastfeeding (EBI) can save 22% of babies who die before the age of 1 month. Early initiation of breastfeeding is still not widely known by the public. Only around 4% of mothers who give birth initiate early breastfeeding in Indonesia. Whether early breastfeeding is successful or not in maternity services, hospitals and community health centers really depends on health workers, namely nurses, midwives or doctors. The aim of this research is to determine the determining factors for the success of EBI implementation at RSU PKU Muhammadiyah Gamping. The design of this research is observational analytic using a cross sectional research approach. The variables used in this research are the independent variable (maternal age, parity, education, employment, type of delivery and gestational age) and the dependent variable (EBI implementation). The sample for this study used the total population (total sampling), namely all mothers giving birth at RSU PKU Muhammadiyah Gamping in 2021 who met the inclusion criteria, numbering 490 respondents. Bivariate analysis uses the chi square test. The research results showed that there was a significant relationship between the type of delivery (p-value 0.033) and gestational age ((p-value 0.000) with the implementation of EBI in the mother. Meanwhile for the factors maternal age (p-value 0.085), parity (p-value 0.151), education (p-value 0.086), and maternal employment (p-value 0.383) showed that there was no significant relationship with the implementation of EBI (p-value <0.05) at RSU PKU Muhammadiyah Gamping. It is recommended that health workers be more plays an active role in providing education and information related to preparation for childbirth, especially readiness to initiate early breastfeeding as a guide for pregnant mothers in the final trimester.